Rationality Test of The Application of Criminal Law on Restitution for Victim Protection in The Criminal Justice System - Faozi, Safik -; Arief, Eva - (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The purpose of this study is to explain the rationality test of restitution imposition for victim protection in the criminal justice system. The ongoing criminal justice system shows a shift in perspective from being offender-oriented to a criminal justice system that also pays attention to aspects of victim protection. Various court decisions show the fulfillment of victim rights through the imposition of restitution, but there are also court decisions that do not impose restitution, so that the criminal justice system still applies victim protection that is abstracted into community protection. This fact is interesting to study from the approach of criminal law policy that is required to be rational. Based on a literature review of the rationality of criminal sanction policies, and the development of a criminal justice model that is accommodative for victim protection, and the juridical-normative method with the specification of inconreto legal research, there are variations in the imposition of restitution, namely being subject to restitution and not being subject to restitution in the ongoing criminal justice system. The rationality test of restitution is based on the realization of the objectives of protection and recovery of victims of sexual violence. The rationality test explains that restitution as a tool/means of realizing the criminal objective of restoring balance that concretely improves the suffering and losses experienced by victims of sexual violence, improves the perpetrator, and resolves the conflict between the perpetrator and the victim. The criminal justice system that applies restitution to victims of sexual violence opens itself up to allow victims to obtain restitution. The procedural criminal justice system provides a means for victims of sexual violence to obtain restitution as a right. The Law on Protection of Witnesses and Victims and the Law on Sexual Violence Crimes, and the Declaration of Basic Principles of Victim of Crime and Abuse of Power have determined restitution to victims of sexual violence both in the trial process and after a court decision after it has permanent legal force.